Training Secondary English Teacher Competence at Toba Regency through Simulation Technique - erikson saragih; Desri Maria Sumbayak; Mahriyuni Mahriyuni; Tiarnida Nababan (English Lecturers and Teachers Association (ELTA), 2023)
The success of the learning process is inseparable from the competence of the teacher. As one of the determining factors for the success of learning, teachers are expected to continue to improve competency and literacy by adjusting to the times. However, with the end of the Covid 19 Pandemic hitting the world, learning platforms that used to use online learning have been changed back to using conventional learning modes. Realizing this transition, the Community Service Team from the Faculty of Cultural Sciences, University of North Sumatra conducted pedagogic training and increased literacy for English teachers throughout Toba Regency, North Sumatra Province from 15 May to 31 May 2023 in Balige, Toba Regency. By adopting an Action research pattern, this program was successfully implemented where the training participants consisted of junior high school teachers whose schools were mostly located in remote and isolated areas. The results of this community service program succeeded in increasing the literacy of English teachers in preparing teaching plans, and teaching practices, and evaluating innovative English lessons. The training participants hope that this activity can be carried out regularly and continuously so that English teachers in the District have good pedagogical literacy and can improve the quality of English learning. Keywords: Improving; Literacy; English Teacher; Simulation